2020
DOI: 10.2147/ijn.s214349
|View full text |Cite
|
Sign up to set email alerts
|

<p>Development of Nanosome-Encapsulated Honokiol for Intravenous Therapy Against Experimental Autoimmune Encephalomyelitis</p>

Abstract: Background: Honokiol has been reported to possess anti-inflammatory and neuroprotective activities. However, the poor aqueous solubility of honokiol limits its clinical application for systemic administration. Purpose: This study aims to develop a novel formulation of nanosome-encapsulated honokiol (NHNK) for intravenous therapy against mouse experimental autoimmune encephalomyelitis (EAE) that mimics human multiple sclerosis. Methods: Nanosomes and NHNK were prepared by using an ultra-high pressure homogeniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
(47 reference statements)
1
16
0
Order By: Relevance
“…Animals were given water and standard mice lab chow (Oriental yeast, Tokyo, JP) ad libitum. Preparation of nanosized liposome-encapsulated honokiol (nHNK) were described earlier, qualitative and quantitative characterization of nNNK was carried out at the department of chemistry at National Taiwan University (NTU Mass Spectrometry Platform) and described earlier [ 17 , 22 ]. Animals were randomly allocated into 4 experimental groups (n = 10–12 for each group) and cisplatin-induced testicular injury mouse model was established as summarized in Figure S2A and described as follow.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animals were given water and standard mice lab chow (Oriental yeast, Tokyo, JP) ad libitum. Preparation of nanosized liposome-encapsulated honokiol (nHNK) were described earlier, qualitative and quantitative characterization of nNNK was carried out at the department of chemistry at National Taiwan University (NTU Mass Spectrometry Platform) and described earlier [ 17 , 22 ]. Animals were randomly allocated into 4 experimental groups (n = 10–12 for each group) and cisplatin-induced testicular injury mouse model was established as summarized in Figure S2A and described as follow.…”
Section: Methodsmentioning
confidence: 99%
“…nHNK (blue closed circle, 100 μL volume) as indicated in the G2. Determination of nanosome honokiol tissue distribution in reproductive organs was carried out as described earlier [ 17 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An et al ( An et al, 2020 ) showed that this compound could reduce demyelination, inflammation, microglial activation, and the expression of IL-2, IFN-γ, IL-1 β, IL-6, and TNF-α in EAE mice. It is expected to become a new drug for the treatment of MS. Honokiol, a nano-liposome developed by Hsiao et al ( Hsiao et al, 2020 ), is a drug that could reduce the number of IL-6 + , Iba-1 + TNF + , Iba-1 + IL-12 p40 + , and CD3 + IFN-γ+cells infiltrating the spinal cord and clearing the inhibitory effect of nanosome-encapsulated honokiol on the infiltration of activated microglia and Th1 cells into the spinal cord. Studies on microglia have shown that resveratrol-treated microglia can significantly inhibit the production of nitric oxide and TNF-α ( Pallares et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…M. officinalis was demonstrated to reduce the long-term effects of status epilepticus induced by kainic acid [13]. Nanosomes used for the encapsulation of HNK were also recently reported to improve the feasibility of HNK for its intravenous administration tailored against autoimmune encelphalomyelitis [14,15]. Additionally, at the cellular level, HNK or magnolol has been shown to induce Ca 2+ mobilization in cortical neurons and in neuroblastoma cells [16], as well as to suppress glutamate-evoked Ca 2+ influx in rat cerebellar granule cells [17].…”
Section: Introductionmentioning
confidence: 99%